Task complexity and jump landings in injury prevention for basketball players - McCormick, B. T. (Strength and Conditioning Journal, 2012)
The prevalence of injury prevention programs continues to increase, but the injury rates remain constant. These programs use a block practice schedule and closed-skill exercises, but games are random and involve open skills. To improve the efficacy of the neuromuscular training programs and trend the injury rate downward, these programs should incorporate motor learning theory. By incorporating more random variable practice, adding complexity to exercises, and lessening the reliance on the visual system for feed-forward motor control, athletes would be prepared better to handle the stresses of game activities.